1992
DOI: 10.1577/1548-8667(1992)004<0001:eordot>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rearing Density on the Stress Response and Growth of Rainbow Trout

Abstract: One-year-old rainbow trout Oncorhynchus mykiss were reared for 8 weeks at a density of either 56 or 267 g fish/L (based on the volume of net-pens), equivalent to density indexes of 2.3 and I l.l g fish/L-cm total fish length), respectively. The fish were held in 0.6 x 0.3-m netpens submerged to a depth of 0.15 m. Two net-pens for each fish density were suspended in each of three 3,040-L circular tanks provided with sufficient flow to maintain loading rates in the tanks at less than 800 g/(L-min). The fish were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 14 publications
6
66
1
3
Order By: Relevance
“…The present study highlighted the negative effect of high stocking density on growth and feed conversion capacity of labeo and catla as observed in previous studies (Ellis et al, 2002;Kebus et al, 1992;Lupatsch et al (2010); Li et al (2012). At this time fish exposed to a higher density showed significantly lower values in total length and weight as indicated by condition factor.…”
Section: Discussionsupporting
confidence: 83%
“…The present study highlighted the negative effect of high stocking density on growth and feed conversion capacity of labeo and catla as observed in previous studies (Ellis et al, 2002;Kebus et al, 1992;Lupatsch et al (2010); Li et al (2012). At this time fish exposed to a higher density showed significantly lower values in total length and weight as indicated by condition factor.…”
Section: Discussionsupporting
confidence: 83%
“…In studies on stress, Pickering et al (1982) utilizing trout (Salmo trutta) and Ellsaesser & Clem (1986) (Ictalurus punctalus), also showed no significant differences in the number of erythrocytes and other hematological parameters. However, Kebus et al (1992) and Iwama (1993) stated that immunodeficiency resulting from the response to stress was due to a negative correlation of the number of circulating lymphocytes with plasma cortisol level. Pickering et al (1982) observed that the simple stress of handling in two specimens of Salmo trutta caused lymphopenia after 8 h, which required 72 h for recovery of lymphocytes to baseline levels.…”
Section: Resultsmentioning
confidence: 99%
“…Huang and Chiu (1997), also argued that since tilapia is a territorial and aggressive fish, their density growth effects arises from their competition for territories, as well as from the permanent stress caused by crowding. This leads to inhibitory fish growth as a result of the fish's physiological alterations elicited by stress responses so that adequate energy is mobilized from the consumed diets (Kebus et al, 1992;Ruane et al, 2002;Ruane and Komen, 2003). Therefore, since slight significant growth responses was observed with higher variances occurring in the hapas with the stocking densities of 50 and 100 fry's, indicated that stocking density had effects on the fry's growth.…”
Section: Discussionmentioning
confidence: 99%